Genetic variation in in-vitro cytokine-induced production of nitric oxide by murine peritoneal macrophages - Zídek, Z; Franková, D; Boubelík, M (Pharmacogenetics, 2000)
Quantitative aspects of the in-vitro interferon (IFN)-gamma-induced nitric oxide (NO) production by peritoneal macrophages of eight inbred strains of mice were investigated. Animals employed in the study can be assorted into three phenotype categories: high, moderate, and low NO-responders. Concentration of nitrites in the 24-h supernatants of cells stimulated with recombinant murine IFN-gamma (25 U/ml) reached the following values (mean +/- SEM; in microM): C57BL/10 (33.7+/-1.88) = C57BL/6 (32.1+/-2.10) > SIL (24.0+/-1.55) > CBA/J (18.1+/-1.79) = C3H/HeN (18.0+/-1.10) > DBA/2 (11.4+/-1.16) = DBA/1 (11.0+/-1.20) = Balb/c (11.0+/-1.16). Approximately 80% of the total variation was found to be controlled by genetic factors. No association between the extent of NO formation and variation in the constitutive expression of macrophage IFN-gamma receptor was observed. Similar magnitude of inter-strain differences was sustained after enhanced NO-stimulation of the cells with IFN-gamma + tumour necrosis factor (TNF)-alpha, but only high (strains BL/10, BL/6, SJL, CBA/J, C3H/HeN) and low (DBA/1, DBA/2, Balb/c) NO-responder phenotypes were detected after the triple cytokine cocktail composed of IFN-gamma + TNF-alpha + interleukin (IL)-10. The strain differences remained unchanged after the supplementation of culture medium with L-arginine or tetrahydrobipopterin. Genetically governed differences in IFN-gamma-induced NO production have been found to be tightly associated with differential expression of inducible nitric oxide synthase mRNA. Possible implications of the findings for various fields of NO biomedical research are discussed.
Keywords: Nitric Oxide; peritoneální makrofágy; myši; inbrední kmeny myší; cytokiny; druhová specificita; Cytokines; Animals; Genetic Variation; Macrophages, Peritoneal; oxid dusnatý; Mice; Mice, Inbred Strains; genetická variace; zvířata; Species Specificity